Risk finance and asset pricing value, measurements, and markets - Tapiero, Charles S. (New York : Wiley, 2010)
"Charles Tapiero, as the head of the biggest financial engineering program in the world and business consultant, has his finger on the pulse of the shift that is coming in financial engineering applications and study. With an eye toward the future, he has crafted a comprehensive and practical book that emphasizes an intuitive approach to the financial and quantitative foundations of financial and risk engineering and its many applications to asset pricing and risk management. Covering the theory from a practitioner perspective, he then applies it to a variety of real world problems. The book presents important techniques to price, hedge, and manage risks in general - while acknowledging the high degree of uncertainty in the real world"-- Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Financial engineering; Financial risk management; Finance -- Mathematical models; Investments -- Mathematical models; Electronic books